Cardiopulmonary Exercise Testing as a Tool for Diagnosing Pulmonary Hypertension in Patients with Dilated Cardiomyopathy. Issue 3 (1st February 2016) - Hirashiki, Akihiro; Kondo, Takahisa; Okumura, Takahiro; Kamimura, Yoshihiro; Nakano, Yoshihisa; Fukaya, Kenji; Sawamura, Akinori; Morimoto, Ryota; Adachi, Shiro; Takeshita, Kyosuke; Murohara, Toyoaki
Abstract : Background: Recently, it has become increasingly recognized that pulmonary hypertension (PH) is a particularly threatening result of left‐sided heart disease. However, there have been few investigations of the impact of cardiopulmonary exercise testing (CPX) variables on PH in dilated cardiomyopathy (DCM). We evaluated the usefulness of crucial CPX variables for detecting elevated pulmonary arterial pressure (PAP) in patients with DCM. Methods: Ninety subjects with DCM underwent cardiac catheterization and CPX at our hospital. Receiver operator characteristic (ROC) analysis was performed to assess the ability of CPX variables to distinguish between the presence and absence of PH. Results: Overall mean values were: mean PAP (mPAP), 18.0 ± 9.6 mmHg; plasma brain natriuretic peptide, 233 ± 295 pg/mL; and left ventricular ejection fraction, 30.2 ± 11.0%. Patients were allocated to one of two groups on the basis of mean PAP, namely DCM without PH [mean PAP (mPAP) <25 mmHg; n = 75] and DCM with PH (mPAP ≥25 mmHg; n = 15). A cutoff achieved percentage of predicted peak VO2 (%PPeak VO2 ) of 52.5% was the best predictor of an mPAP ≥25 mmHg in the ROC analysis (area under curve: 0.911). In the multivariate analysis, %PPeak VO2 was the only significant independent predictor of PH (Wald 6.52, odds ratio 0.892, 95% CI 0.818–0.974; P = 0.011). Conclusions: %PPeak VO2 was strongly associated with the presence of PH in patients with DCM. Taken together, these findings indicate that CPX variables could be important for diagnosing PH in patients with DCM.